2011
DOI: 10.1186/1744-8069-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Cav3.2 T-Type Calcium Channel in Thalamic Neuron Discharge Patterns

Abstract: BackgroundMice that have defects in their low-threshold T-type calcium channel (T-channel) genes show altered pain behaviors. The changes in the ratio of nociceptive neurons and the burst firing property of reticular thalamic (RT) and ventroposterior (VP) neurons in Cav3.2 knockout (KO) mice were studied to test the involvement of thalamic T-channel and burst firing activity in pain function.ResultsUnder pentobarbital or urethane anesthesia, the patterns of tonic and burst firings were recorded in functionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
0
30
1
Order By: Relevance
“…This observation could be explained by the use of the anesthetic drug ketamine, a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist (Gunduz-Bruce 2009) that is likely to affect the specific NMDA currents in PV-positive interneurons (Korotkova et al 2010). In contrast to the previous study of in vivo recording in the RTN by Liao et al (2011) we observed lower firing rates (on average, 3.7 vs. 8.6 spikes/ s). In addition to the differences in the anesthetic procedures mentioned above, our studies differed in the type of electrodes that were used, in the sorting procedure of the waveforms of the electrophysiological signals, and in the sample size (n ϭ 93 in this study vs. n ϭ 17).…”
Section: Four Firing Types Characterize the Mouse Rtncontrasting
confidence: 54%
See 4 more Smart Citations
“…This observation could be explained by the use of the anesthetic drug ketamine, a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist (Gunduz-Bruce 2009) that is likely to affect the specific NMDA currents in PV-positive interneurons (Korotkova et al 2010). In contrast to the previous study of in vivo recording in the RTN by Liao et al (2011) we observed lower firing rates (on average, 3.7 vs. 8.6 spikes/ s). In addition to the differences in the anesthetic procedures mentioned above, our studies differed in the type of electrodes that were used, in the sorting procedure of the waveforms of the electrophysiological signals, and in the sample size (n ϭ 93 in this study vs. n ϭ 17).…”
Section: Four Firing Types Characterize the Mouse Rtncontrasting
confidence: 54%
“…This might be caused either by the absence of PV or by the homeostatic compensation mechanisms underlying the altered cellular distribution of Ca v 3.2. Interestingly, the firing phenotype of PVKO RTN neurons showed large similarities to the one seen in Ca v 3.2 KO neurons (Liao et al 2011): the burst duration was increased, caused by a larger interval between spikes, without affecting the spike number within a burst. Ablation of the Ca v 3.2 channel, a LVA channel type characterized by fast activation and inactivation kinetics (Kozlov et al 1999), provokes I T to be mediated by the "slower" variant, Ca v 3.3, hence leading to the observed phenotype.…”
Section: Medium Bursting Rtn Neurons Are Prevalent In the Absence Of Pvmentioning
confidence: 82%
See 3 more Smart Citations